Securitizing and greening the contested, climate-changed ocean: benefits, risks and governance pathways for integrating defense into climate-smart marine spatial planning - Tafon, Ralph (Frontiers in Ocean Sustainability, 2026)
Oceans are increasingly shaped by climate change, biodiversity loss, geopolitical tensions and maritime crime and insecurity. Climate-smart marine spatial planning (CSMSP) has emerged as a governance framework to integrate climate action, conservation, and equity into ocean planning. However, defense institutions–key actors in maritime security and major greenhouse gas emitters–remain absent from CSMSP discourse. This paper argues that integrating defense into CSMSP offers strategic and climate benefits: minimizing defense-driven offshore wind cancellation and thus accelerating approval, safeguarding environmental protection and undersea critical energy infrastructure, accelerating decarbonization through the military's green transition, and addressing the defense emissions gap. Yet, integration carries significant risks: power asymmetries, spatial exclusion, ecological harm, and militarization of green energy. To reconcile security imperatives with sustainability, transparency and equity, the paper proposes governance pathways: transparent data sharing, conflict-resolution and co-existence protocols, and defense marine zoning. “However, the paper warns that while green defense initiatives have climate benefits, there are reasons to curb our enthusiasm”. Specifically, rising global military spending and the resultant mineral-intensive extractivism to support war-readiness threaten to overshadow these benefits by locking in carbon-heavy supply chains and amplifying upstream emissions, environmental degradation, and social disposability. Aligning national security with climate security thus requires more than technological greening: it requires transparent cradle-to-grave emissions, and strategic restraint in defense spending, war-readiness, and material efficiency. Ultimately, integrating defense into CSMSP is not merely a technical exercise but a normative challenge that will determine whether ocean governance advances sustainability and transparency or succumbs to securitized emissions and green extractivism.